Need for cognition and rumour theory in post-revolutionary Egypt - Ashour, Lina (AUC Knowledge Fountain, 2015)
Egyptian society went through a number of significant changes between 2011 and 2015 as a result of the January 25 Revolution. Beyond the political implications, there have also been shifts in the social and psychological motivations behind the way people consume media and share information. This included a sharp increase in the public’s interests in political affairs after spending years of being generally apathetic. This paper examines whether this could be described as an increase in Need for Cognition on a social level and whether this has affected the spread of rumours in Egyptian society. Through in-depth interviews with a convenience sample of media professionals, the evolving relationship the Egyptian people have with their own sense of identity, the government, and media outlets is examined.